Biodegradation potential of ofloxacin and its resulting transformation products during photolytic and photocatalytic treatment - Vasquez Christodoulou, Marlen; Hapeshi, Evroula; Fatta-Kassinos, Despo; Kümmerer, Klaus (My University, 2013)
The release of pharmaceuticals in the environment, as parent compounds, metabolites and transformation products, and the consequent risks posed to living organisms due to the unintended exposure of the latter to these chemicals are nowadays of increasing scientific concern. The development of advanced oxidation processes able to degrade these substances is in the core of the current research objectives, the main target being the removal of these compounds from wastewaters. Often the focus is on the removal of the parent compound only. However, these processes can form transformation products. Knowledge on the risk related to such transformation products is scarce. Among others, knowledge on their toxic effects and their biodegradability is of importance not only when they are present in the environment but also for the assessment of the advanced oxidation processes' efficiency applied for their degradation. Photolytic (UV irradiation) and photocatalytic treatment (UV irradiation in the presence of TiO(2)) of the fluoroquinolone ofloxacin were applied, and the biodegradability of the formed products was investigated using the Closed Bottle test (OECD 301 D). Various transformation products, formed both during the photo(cata)lytic treatment and the Closed Bottle test, were identified using chromatographic analysis with an ultra high-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) system. The transformation products formed during the phototreatments were found to be non-readily biodegradable as the biodegradation percentages were close to zero. The persistence of the various photo(cata)lytic transformation products during the Closed Bottle test may be attributed to the fluorine present in all the transformation products formed. The transformation products identified suggest that two transformation routes were present: decarboxylation and opening of the piperazinyl ring. Interestingly, it was observed that in the presence of a readily biodegradable carbon source (sodium acetate), the biodegradation percentage increased drastically for some of the photolytically treated samples. This was not the case for the photocatalytically treated samples, in which also mineralization of the parent compound was achieved faster. Further research is needed, however, in order to increase the understanding of the conditions that may lead to less potent and persistent substances during the application of such engineered or natural processes.
Keywords: Biodegradation; Closed Bottle test; Fluoroquinolone; Ofloxacin; Photolysis; Photocatalysis; Transformation product